Validation of the SDM Process Scale to Evaluate Shared Decision-Making at Clinical Sites. (November 2021) - Fowler, Floyd J.; Sepucha, Karen R.; Stringfellow, Vickie; Valentine, KD
The Shared Decision-Making (SDM) Process scale (scored 0-4) uses 4 questions about decision-making behaviors: discussion of options, pros, cons, and preferences. We use data from mail surveys of patients who made surgical decisions at 9 clinical sites and a national web survey to assess the reliability and validity of the measure to assess shared decision-making at clinical sites. Patients at sites using decision aids to promote shared decision-making for hip, knee, back, or breast cancer surgery had significantly higher scores than national cross-section samples of surgical patients for 3 of 4 comparisons and significantly higher scores for both comparisons with "usual care sites." Reliability was supported by an intra-class correlation at the clinical site level of 0.93 and an average correlation of SDM scores for knee and hip surgery patients treated at the same sites of 0.56. The results document the reliability and validity of the measure to assess the degree of shared decision-making for surgical decisions at clinical sites.